Microlicia frankii (Melastomataceae: Microlicieae), a new species from Serra do Cipó, Minas Gerais, Brazil - Pacifico, Ricardo; Fidanza, Karina (Phytotaxa, 2018)
Microlicia frankii is described, illustrated, and compared with M. ericoides and M. juniperina. It is distinguished by its reduced habit (3–15 cm in height), leaves linear-oblong 2–5 mm long, glandular-punctate on both surfaces, flowers apical and solitary, calyx lobes narrowly-triangular 3.5–7 mm long, petals magenta, isomorphic stamens, and tetrasporangiate thecae. The new species is probably endemic to Serra do Cipó, Minas Gerais, Brazil.